Penilaian Grade dan Nilai Ekonomi Kambing Peranakan Etawa Kaligesing dalam Kontes Ternak - Ica Ayu Wandira; Jingga Raya Ramuni; Muhammad Dohi; I Nyoman Sadia; Ine Karni (LPPM Universitas Mataram, 2026)
Kaligesing Peranakan Etawa (PE) goats are local livestock with high economic value and are widely raised as contest animals. This study aimed to evaluate shoulder height-based grades, grade distribution, selling value, and the relationships among age, shoulder height, grade, and price of Kaligesing PE goats in a livestock contest in Mertak Tombok Village, Central Lombok. This study used a quantitative descriptive survey method with 54 goats, comprising 39 males and 15 females. Data were collected through direct observation, shoulder-height measurements, contest data recording, and interviews. The data were analyzed using descriptive statistics and Pearson correlation analysis. The results showed that 41 goats met the age criteria for grade assessment, while 13 goats aged 0–<4 months were not graded. Male goats were dominated by grade A, accounting for 80.65%, whereas female goats were dominated by grade B, accounting for 80.00%. The highest average shoulder height and price were found in male goats aged >12–36 months, at 101.40 cm and IDR 71,533,333, respectively. Age had a very strong correlation with shoulder height and price, while shoulder height had a strong to very strong correlation with grade and selling price. Therefore, shoulder height can serve as a practical indicator for the initial selection of Kaligesing PE goats for contests and breeding